Combining Ability and Gene Action Studies for Grain Yield and Quality Parameters in Yellow Seeded Maize (Zea mays L.) Using Line×Tester Crosses - Khan, Shaukeen; Dadheech, Amit; Dubey, R. B.; Bharti, Baudh (International Journal of Bio-resource and Stress Management, 2016)
The present investigation was carried out at All India Co-ordinated Maize Improvement Project, MPUAT, Udaipur. 15 inbred lines were crossed with three testers viz; (EI-561-1, EI-586-2 and EI-708-2) in line×tester mating design to develop 45 hybrids. These 45 hybrids, 18 parents and along with the three checks were evaluated in randomized block design with three replications during kharif 2014. The combining ability analysis revealed that the mean squares among parents were highly significant for yield and all quality characters indicating presence of genetic variability among the parents. The variance due to SCA was higher than GCA by the σ2 GCA/σ2 SCA ratio being less than one for the all characters, suggesting significant role of non -additive gene actions like dominance, epistasis and other interaction effects in the expression of these characters. Parents L1, L15, L5, L4 and L7 were the good general combiners and genetically worthy parents, as they contributed favourable genes for grain yield and quality traits. Whereas the crosses, L4×T3 followerd by L7×T3, L15×T2 and L10 ×T2 for grain yield plant-1, L8×T2, L9×T3 for oil content and L8×T3, L15×T2, L5 ×T2, L5×T1 for protein content were identified as most promising crosses. based on SCA effects, better per se and both or one of the parents with high GCA for grain yield and quality traits also, could be exploited profitably for yield quality traits in maize.